(untitled) (Research, Society and Development, 2021)
Objective: To evaluate how nurses perceived their work environment during the pandemic. Method: This is a descriptive and qualitative research, by discourse analysis through a questionnaire sent online sent by conversation application. Data were collected from August to September 2021. Results: It was observed that even with training/training, nurses relate fear, stress and others, as early factors of mental illness, also realizing how the factors of increased flow of patients increase the burden of stress inside and outside work, leading to mental suffering. Conclusion: Considering the nursing professional, the relevance of addressing the theme to other professionals and students in the area is emphasized. It was expected with the results to contribute to the reflection of the role of nurses and the emotional and physical load that these professionals carry.